Les pollutions atmosphériques urbaines de proximité à l’heure du Développement Durable - Séverine Frère; Isabelle Roussel; Aymeric Blanchet (Développement Durable et Territoires)
Proximity atmospheric pollutions linked to a dense urban fabric are the subject of nuisance felt and denounced by city dweller. From a historic point of view, stories of noxious odours in urban centers are associated to industrial activities. While very attentive to industrial pollution during the hygienist period, city politics have turned away from atmospheric urban pollution issues when air quality networks have taken charge of measurement and monitoring. The measurement of invisible and toxic pollution have remained in a technical domain until recent years, when progressively, atmospheric pollutions have become a politic issue. Despite the phenomenon of proximity atmospheric pollution recurrence and the increase of complaints by inhabitants, institutional response hasn’t been formalised yet to define a processing procedure and answers to give to the complaints. A complaint survey, done in Paris and the Nord-Pas-de-Calais region, especially in the Artois area, demonstrates this fully.Recognition and complaint processing of proximity atmospheric pollutions nuisances are still problematic and require time to be duly recognized, Drocourt being a clear example of this problem. Moreover, these nuisances are still more difficult to evaluate and quantify, the principle of a sustainable development hasn’t put is on mark in the solutions which outline now. Solutions use more a remediation logic to solve the problem than a safety-first precaution. The subject of environmental nuisances and the complaints they generate has an ambiguous nature: between health and quality of life, industry and urban life situation, between nuisance and toxicity, trouble and Atmospheric pollutions of proximity. Their ambiguous nature allows to ask for a management of nuisance and atmospheric pollution with a proximity approach, close to the citizen’s preoccupations and with sustainable development in mind.